2023
DOI: 10.22495/cgobrv7i3p6
|View full text |Cite
|
Sign up to set email alerts
|

Workplace conflict and the productivity of employees in the healthcare sector: A case study

Francis Ezieshi Monyei,
Pamela Nkechi Ezinwa,
Emmanuel Kalu Agbaeze
et al.

Abstract: The study aims at examining the impact of workplace conflict on employee productivity in the healthcare industry. Workplace conflict is a dysfunctional stressor that undermines the endeavours, and performances of any workplace (Adewole & Adebola, 2010). While it adopted the descriptive survey design for the investigation, the participants were 4541 comprising senior and junior staff members from the five selected Federal Health Institutions in Enugu State, Nigeria (namely: University of Nigeria Teaching Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…A lot of researches concern the approaches to resolving conflicts in the workplace (Liao & Pandeli, 2023). We found that resolving conflicts and addressing social tensions in the workplace is crucial for maintaining a healthy and productive work environment (Ferine et al, 2021;Monyei et al, 2023). Figure 2 shows some approaches to help manage and resolve such issues.…”
Section: Team-buildingmentioning
confidence: 99%
“…A lot of researches concern the approaches to resolving conflicts in the workplace (Liao & Pandeli, 2023). We found that resolving conflicts and addressing social tensions in the workplace is crucial for maintaining a healthy and productive work environment (Ferine et al, 2021;Monyei et al, 2023). Figure 2 shows some approaches to help manage and resolve such issues.…”
Section: Team-buildingmentioning
confidence: 99%